2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6943260
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of a quadruped robot model with impedance control: Self-stabilizing high speed trot-running and period-doubling bifurcations

Abstract: Abstract-The MIT Cheetah demonstrated a stable 6 m/s trot gait in the sagittal plane utilizing the self-stable characteristics of locomotion. This paper presents a numerical analysis of the behavior of a quadruped robot model with the proposed controller. We first demonstrate the existence of periodic trot gaits at various speeds and examine local orbital stability of each trajectory using Poincarè map analysis. Beyond the local stability, we additionally demonstrate the stability of the model against large in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The dynamic stability criteria of legged robots are still in question. Because the locomotion of a legged robot is typical periodic motion, Poincarè return map analysis has been widely adopted to evaluate locomotion stability [22,[112][113][114], from the relatively simple SLIP control model [97] to more complicated models involving specific configuration such as hybrid leg mechanisms [6]. SLIP model.…”
Section: Dynamics-based Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic stability criteria of legged robots are still in question. Because the locomotion of a legged robot is typical periodic motion, Poincarè return map analysis has been widely adopted to evaluate locomotion stability [22,[112][113][114], from the relatively simple SLIP control model [97] to more complicated models involving specific configuration such as hybrid leg mechanisms [6]. SLIP model.…”
Section: Dynamics-based Controlmentioning
confidence: 99%
“…Furthermore, all control parameters except the virtual ground-penetration depth can be predetermined by preliminary experiments. The Cheetah 1 robot using this kind of control model with fixed control parameters can yield self-stabilizing trot-running at speeds up to 6 m/s [113].…”
Section: Software Architecturementioning
confidence: 99%
“…Our “throw-and-catch” gait transition strategy may instantly destabilize the locomotion dynamics, and thus the performance depends on the stability and basin of attraction of each gait pattern. The stability of the trot gait with the proposed controller was already analyzed in our previous work (Lee et al., 2014). In the simulation, therefore, we present two important results to evaluate stability of the gallop gait: (1) the eigenvalues of the linearized Poincaré map of the galloping limit cycle to discuss local orbital stability; and (2) the response of the gallop gait to wide-range perturbations.…”
Section: Simulation Verification On the Performance Of The Developmentioning
confidence: 99%
“…In our previous work (Hyun et al, 2014), we demonstrated the 6 m/s trot running of the MIT Cheetah I, using the “proprioceptive impedance control”. 2 The detailed analysis of the dynamic characteristics is in Lee et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Legged robots' high-speed locomotion is one of the challenging issues in robotic research. [11][12][13][14] However, few studies covered the qualitative change of leg stiffness with the running speed increasing.…”
Section: Introductionmentioning
confidence: 99%